Perioperative Use of Serotonin Reuptake Inhibitors and Risks for Adverse Outcomes of Surgery - Auerbach, Andrew D. (2013)
BACKGROUND: Single site studies have described an association between selective serotoninreuptake inhibitors (SSRI) and adverse outcomes of surgery. We sought to determine whether perioperative use of SSRIs is associated with adverse outcomes of surgery in a national sample of patients. METHODS: Retrospective study of 530,416 patients 18 or older who underwent major surgery between 2006 and 2008 at 375 US Hospitals. We used multivariable hierarchical models to estimate associations between SSRI use and our outcomes. Pharmacy data were used to determine whether a patient received an SSRI in the perioperative period. Our primary outcomes included in-hospital mortality, length of stay, readmission at 30 days, bleeding events, transfusions, and incidence of ventricular arrhythmias. RESULTS: Patients receiving SSRI medications were more likely to have obesity, chronic pulmonary disease, or hypothyroidism (p<0.001 for each), and more likely to have depression (41.0% vs. 6.2%, p<0.0001). After adjustment, patients receiving SSRIs had higher odds for inhospital mortality (Adjusted Odds [AOR] 1.20 (1.07, 1.36), bleeding (AOR 1.09, 95% 1.04, 1.15), and readmission at 30 days (AOR 1.22, 95% CI 1.18, 1.26). Similar results were observed in propensity-matched analyses, though risk of inpatient mortality was attenuated among patients with depression. Sensitivity analyses suggest that, in order to invalidate our results, an unmeasured covariate would have to have higher prevalence and be more strongly associated with mortality than any covariate included in our models. CONCLUSIONS: Receiving SSRIs in the perioperative period is associated with higher risk for adverse events. Determining whether patient factors or SSRIs themselves are responsible for elevated risks require prospective study.